2016
DOI: 10.5539/jedp.v6n1p157
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Magnitude Skills in 6-Years-Old Children: Exploring Specific Associations with Components of Executive Function

Abstract: Little is known about how children learn to associate numbers with their corresponding magnitude and about individual characteristics contributing to performance differences on the numerical magnitude tasks within a relatively homogenous sample of 6-year-olds. The present study investigated the relationships between components of executive function and two different numerical magnitude skills in a sample of 162 kindergartners. The Symbolic Number Line was predicted by verbal updating and switching, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In that study, Hornburg et al (2018) found concurrent associations between relational language and counting, cardinal knowledge, number comparison, and number ordering when controlling for children's general language skills. Two important extensions of these findings are to (1) investigate the longitudinal association between relational language and distinct aspects of early numeracy while controlling for related cognitive correlates, such as general verbal knowledge (LeFevre et al, 2010) and executive function (EF) skills (Gashaj et al, 2016), and (2) delineate the potential mechanisms underlying the association between relational language and math during early childhood. These extensions offer the additional value of replicating the finding of unique associations between relational language and aspects of numeracy skills.…”
Section: Relational Language and Mathematical Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study, Hornburg et al (2018) found concurrent associations between relational language and counting, cardinal knowledge, number comparison, and number ordering when controlling for children's general language skills. Two important extensions of these findings are to (1) investigate the longitudinal association between relational language and distinct aspects of early numeracy while controlling for related cognitive correlates, such as general verbal knowledge (LeFevre et al, 2010) and executive function (EF) skills (Gashaj et al, 2016), and (2) delineate the potential mechanisms underlying the association between relational language and math during early childhood. These extensions offer the additional value of replicating the finding of unique associations between relational language and aspects of numeracy skills.…”
Section: Relational Language and Mathematical Skillsmentioning
confidence: 99%
“…First graders’ ability to hold information in working memory is correlated with their performance on seriating items based on size and sets based on quantity (Nunes et al, 2007). Preschoolers’ ability to ignore irrelevant information while remembering relevant information is correlated with their concurrent performance on number comparison (Gashaj et al, 2016; Purpura, Schmitt, et al, 2017). Four‐ to seven‐year‐olds’ ability to hold information in working memory and flexibly shift between rules is correlated with their concurrent performance on number line estimation (Friso‐van den Bos et al, 2014; Gashaj et al, 2016).…”
Section: Relational Language and Mathematical Skillsmentioning
confidence: 99%
See 1 more Smart Citation